Impact of the Word “Right” in Environmental Law on the Environment Based on Human Rights Concept - Seketi, Paringga Berlianna Byatara (Balobe Law Journal, 2025)
Introduction: This paper reviews the impact of the word “rights” in environmental regulations, namely Law Number 32 of 2009. The word “rights” in the regulation causes the community as legal subjects but unfamiliar with the law to assume that rights are an option not something that must be fulfilled to fulfill the human rights of the community as individuals.Purposes of the Research: This paper aims to ensure that the word “rights” in the Environmental Law is no interpreted as option but necessity to be fulfilled and guaranteed its realization by the state.Methods of the Research: Using normative legal research consisting of primary legal materials, namely the 1945 Constitution and Law Number 32 of 2009 concerning Environmental Protection and Management. Secondary legal materials are books, research results, legal journals. The method of thinking used is deductive.Results of the Research: Based on Theory of Integrating Universality and Pluralism, the results of the author's research show that origin of the community understands the word “rights” in environmental laws as an option because in the 1948 Universal Declaration of Human Rights there are economic, social and cultural rights, all of which must be balanced. The word “rights” in environmental laws provides an opening so that the economy and culture must also be considered in running life. Furthermore, the level of education, economy and culture in society also influences the neglect of the “right” to a clean and healthy environment for the community.